“Material that Has Suggested Real Life”: The Heritage Collection of Mészöly Miklós at the Petőfi Literary Museum - MÁRJÁNOVICS, Diána (Anafora, 2023)
The paper discusses the legacy of the renowned Hungarian writer, Miklós Mészöly, in the literary and political context of the ’50s and ’60s of the last century. The research is based on genetic criticism  on the exploration of on autograph diary notes, written drafts, various original manuscripts  and focuses on previous versions of Mészöly’s final texts. The study deals with a specific part of Mészöly’s wide-ranging œuvre. The paper focuses on the early prose works Az atléta halála (Death of an Athlete, 1966), Saulus (Saul, 1968), and Pontos történetek, útközben (Exact Stories on the Road, 1970) that have had a poetically and theoretically stimulating effect on the Hungarian contemporary authors and scholars. The paper includes several important and formerly unknown documents from the Mészöly heritage collection, kept in the Petőfi Literary Museum, which revise the interpretations of Mészöly’s above-mentioned works.